West Bank and Gaza Strip : Recent Economic Developments and Prospects and Progress in Institution Building; Background Paper Issued in Connection with the 1995 Article IV Consultation with Israel. (IMF Staff Country Reports; Country Report, 1995)
This paper reviews institutional arrangements in the West Bank and Gaza Strip (WBGS), the structural features of the economy, and macroeconomic developments and prospects during the 1990s. The paper discusses the technical assistance that the IMF staff has been providing in response to requests from the Palestinian Authority and the donor community in the areas of fiscal policy and administration, banking, statistics, and training. A review of IMF-World Bank collaboration and donors' financial assistance is also presented.